Quality evaluation of technical specifications on civil works - Carlos Saldaña; Dayanna Roman; Tito Castillo; Alexis Andrade; Cesar Mora (NOVASINERGIA)
Technical specifications (TS) comprise all the items of a construction project. Each TS must have seven primary sections providing adequate and accurate information for the project's execution. However, construction delays and over costs have been reported as being generated by deficiencies in TS definition during the planning phase of the construction projects. Despite the project's effects, the quality of TS has been scarcely studied to establish its main failures. This research aimed to evaluate the quality of the TS in civil works based on the expectation-reality relationship. For this purpose, an on-site evaluation was carried out during working days in a total of 176 items being executed or recently executed in 30 projects located in Zone 3 of Ecuador. SPSS software was used to process and interpret data. The results show a 39.81% quality of the TS for the analyzed sample, which could cause the increase in cost and term that has been evidenced in many public construction contracts.